Linking TLR-7 Signaling to Downregulation of Placental P-Glycoprotein: Implications for Fetal Drug Exposure - Mario Riera-Romo; Eliza R McColl; Micheline Piquette-Miller (Pharmaceutics, 2025)
Background/Objectives: Activation of the Toll-like receptor 7 (TLR-7) plays an important role in the pathogenesis of many autoimmune diseases and viral infections. Although we have previously observed inflammation-mediated dysregulation of placental transporters, the role of TLR-7 has not been examined. Using the TLR-7 agonist, imiquimod (IMQ), we evaluated transporter expression in IMQ-treated pregnant rats and ex vivo in cultured rat placental explants. Methods: We administered 5 mg/kg (IP) of IMQ to pregnant Sprague Dawley rats on gestational day (GD) 14. The expression levels of inflammatory biomarkers and transporters were measured in maternal and fetal tissues by qRT-PCR and immunodetection methods, and effects on the placental proteome were assessed using LC/MS/MS. The involvement of TLR-7 was confirmed in rat placental explants. Results: IMQ administration resulted in Irf7 induction and increased levels of IL-6, Tnf-α, and type-I/II interferon pathways in maternal liver and placenta, which is consistent with TLR-7 activation. Proteomic profiling revealed IMQ-mediated activation of pathways involved in immune response, vesicle trafficking, and oxidative stress. Significantly decreased placental, hepatic, and renal protein expression of P-glycoprotein (PGP) was seen in the IMQ group. Likewise, TLR-7 activation using single-stranded RNA resulted in an induction of inflammatory biomarkers and downregulation of PGP in rat placental explants. Conclusions: We demonstrated that the activation of TLR-7 signaling during pregnancy reduces the expression of PGP in placenta and maternal tissues. Further studies are warranted, as decreased protein expression could result in decreased activity and altered fetal exposure to its substrates.